2019
DOI: 10.3390/cells8111337
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 and Akt2 Isoforms Play Distinct Roles in Regulating the Development of Inflammation and Fibrosis Associated with Alcoholic Liver Disease

Abstract: Akt kinase isoforms (Akt1, Akt2, and Akt3) have generally been thought to play overlapping roles in phosphoinositide 3-kinase (PI3K)-mediated-signaling. However, recent studies have suggested that they display isoform-specific roles in muscle and fat. To determine whether such isoform-specificity is observed with respect to alcoholic liver disease (ALD) progression, we examined the role of Akt1, Akt2, and Akt3 in hepatic inflammation, and pro-fibrogenic proliferation and migration using Kupffer cells, hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…The major phenotype of the LY294002-treated tibiae was represented by a 45% reduction in the length of the hypertrophic zone [41]. In addition, AKT1 and AKT2, but not AKT3, were reported to inhibit fibrogenesis in hepatocytes and HSC [42]. Besides, previous studies have revealed that the PI3K/AKT signaling pathway is associated with hypertrophy and fibrosis in different tissues such as cardiac hypertrophy [43] and liver fibrosis [18].…”
Section: Discussionmentioning
confidence: 97%
“…The major phenotype of the LY294002-treated tibiae was represented by a 45% reduction in the length of the hypertrophic zone [41]. In addition, AKT1 and AKT2, but not AKT3, were reported to inhibit fibrogenesis in hepatocytes and HSC [42]. Besides, previous studies have revealed that the PI3K/AKT signaling pathway is associated with hypertrophy and fibrosis in different tissues such as cardiac hypertrophy [43] and liver fibrosis [18].…”
Section: Discussionmentioning
confidence: 97%
“…and AKT2, but not AKT3 were reported to inhibit fibrogenesis in hepatocytes and HSC [39]. Besides, previous studies had revealed that the PI3K/AKT signaling pathway was associated with hypertrophy and fibrosis in different tissues such as cardiac hypertrophy [40] and liver fibrosis [18].…”
Section: Discussionmentioning
confidence: 99%
“…As previous studies, Akt1 is an important regulator for cell growth and proliferation [20,21]. In order to explore the function of Akt1 gene on NST of PCa cells, we developed stable Akt1 silencing Pca cells.…”
Section: Discussionmentioning
confidence: 99%